Work life, relationship, and policy determinants of health and well-being among Filipino domestic Workers in China: a qualitative study - Brian J. Hall; Melissa R. Garabiles; Carl A. Latkin (BMC, 2019)
Abstract Background Overseas Filipino workers (OFWs) comprise one of the largest populations of migrant workers globally. Within China, they represent the largest group of imported domestic workers. Little is known about their working conditions or how this might affect their health and wellbeing. Methods This qualitative study explored the working conditions and risk factors for poor health in a sample of temporary female Filipino domestic workers in Macao, China. Focus group discussions with female domestic workers (n = 22) and in-depth interviews with key informants (n = 7) were conducted. Results Domestic workers reported physical (e.g., hypertension, chronic pain, diabetes, poor sleep), and mental health problems (depression, anxiety), and addictive behaviors (gambling, alcohol misuse), along with significant structural, linguistic, financial, and cultural barriers to healthcare access to address these concerns. Adverse working conditions including poor treatment and abuse by employers, lack of privacy and inadequate sleeping areas in employers' homes or in crowded boarding houses, language barriers, inadequate and poor enforcement of labor protections, and discrimination. Domestic workers also cited exorbitant agency fees and remittances causing significant financial stress. Kinship network ties with family members back home were fraught with infidelity, difficulty parenting, misuse of remittances, and family misconceptions of domestic workers' situation abroad. Lack of quality social support and peer social networks exacerbated these conditions. Conclusions In this sample of Filipino migrant domestic workers, stressors experienced within the host country were commonly reported. Indebtedness and low salaries limits social mobility. Psychosocial and policy-level interventions are needed to improve the health and wellbeing of this population of migrant women.